δ13C OF PLANT-DERIVED N-ALKANES IN SOIL PARTICLE-SIZE FRACTIONS - Cayet C.; Lichtfouse E. (My University, 2001)
Soil organic carbon can be labelled at natural abundance by the cultivation of C4 plants, e.g. maize, on soils which have been previously cropped with isotopically distinct C3 plants, e.g. wheat. Particle-size fractions from soils cultivated for 23 years either with maize or wheat have been analysed for C and N contents, and for δ 13C values of bulk C and of plant-derived n-alkanes (C29, C31). The amount of maize-derived organic components has been calculated by isotope balance. After 23 years of maize cropping, δ 13C values of n-alkanes from the same soil sample increase with particle size. The results have two implications. First, the input of leaf wax n-alkanes into the soil is occurring preferentially via large particles. Second, in a same soil sample, the C31 n-alkane from the 200-2000 μm particle-size fraction is younger than the C31 n-alkane from the 50-200 and 0-50 μm fractions. In this respect, 13C analysis represents a method of relative dating of individual compounds.
Keywords: SOIL N-ALKANE; 13C; PARTICLE-SIZE; ZEA MAYS; TRITICUM AESTIVUM; GC-C-IRMS